2021
DOI: 10.37680/muharrik.v4i02.1011
|View full text |Cite
|
Sign up to set email alerts
|

Media, Consumerism and the Environment: The Relationship of Media and Consumptive Behavior of Urban Society to Environmental Damage

Abstract: In a few decades, the media has become the locomotive that controls the consumptive behavior of society, especially in urban areas. Massive media that aggressively offers easy access to meet all kinds of urban community needs encourages consumerism. The trend of consumerist urban lifestyle in the end must take consequences for environmental damage. As with Fast Food and Fashion which results in increased industrial production, the energy required for production is higher. At the same time, the energy used also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Various studies have shown that 97 percent of the scientific consensus agrees that global warming is occurring and is largely caused by human activities [7]. Human activities that are driving factors of global warming are consumptive lifestyles and the use of products that are difficult to decompose [8][9][10]. Humans in carrying out their lives cannot be separated from consuming products according to their daily needs.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that 97 percent of the scientific consensus agrees that global warming is occurring and is largely caused by human activities [7]. Human activities that are driving factors of global warming are consumptive lifestyles and the use of products that are difficult to decompose [8][9][10]. Humans in carrying out their lives cannot be separated from consuming products according to their daily needs.…”
Section: Introductionmentioning
confidence: 99%